Determinants of Islamic Bank Non-Performing Financing By Financing Contract (Case Study: Bank BRIsyariah Private Company) - Moch. Hadi Santoso; Hermanto Siregar; Dedi Budiman Hakim; Mulya E. Siregar (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
This study integrates the determinant factors of external and internal factors that affect the Bank BRISyariah Non-Performing Financing (NPF) in the period of Quarter I 2010 to Quarter IV 2017 by using multiple regression analysis. The external variables themselves consist of Inflation Rate, Benchmark Interest Rate/BI Rate, Economic Growth and USD/IDR Exchange Rate while internal factors consist of Return on Assets (ROA), Net Income Margin (NIM), Growth Financing, Financing to Deposit Ratio (FDR), Bank Rating (consisting of Good Corporate Governance, Risk Profile, Profitability and Capital) and NPF Management/NPF handling. Based on this methodology, the results with multiple regression analysis indicate that under existing contracts or financing contracts, the influencing factors are that 1) NPF in murabahah contract is influenced by bank rating - good corporate governance, exchange rate and benchmark interest rate; 2) NPF in ishtisna contract is influenced by bank rating - risk profile, bank rating - good corporate governance, NPF handling and inflation rate; 3) NPF in qardh contract is influenced by bank rating - rentability; 4) NPF in mudharabah/musyarakah contract is influenced by the rate of inflation; 5) NPF in ijarah contract is influenced by bank rating - risk profile, bank rating - good corporate governance, bank rating - rentability, financing growth and inflation rate. This research produces external and internal factors that need to get attention in order to handle non-performing financing based on financing contract better.Keywords: non-performing financing, sharia bank, external factors, internal factors, financing contract